(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2019)
يهدف البحث إلى إبراز مشكلات تطوير النظام المحاسبي للشركة العامة للبناء عبر تحليل هذا النظام، وتصميمه وإبراز أهمية اختيار المنهج السليم في عملية التحليل لضمان الموثوقية والحماية للبيانات والمعلومات وذلك باستخدام أحد أهم مداخل إنشاء نظام المعلومات المحاسبي وتطويره، وقد تم اقتراح تصميم النظام وفق أحدث الطرق المتبعة عالمياً (Merise) وخلص البحث إلى عدد من النتائج والتوصيات ومن أهمها: ضرورة إتمام عملية المعالجة الآلية على مرحلتين: المرحلة الأولى: جمع الوثائق وأرشفتها وتحليلها، والمرحلة الثانية: استخدام المعالجة الآلية الشاملة حيث يصبح الموظفون أكثر تقبلاً للفكرة فيساهمون في تقديم النصائح والمعلومات المفيدة للجهة الدراسة. This research aims at highlighting problems of developing the accounting system of the general company of construction through analyzing this system and its design, besides emphasizing the importance of choosing the right analytic approach to ensure credibility and protection of data and information. This is done through using a very important entry to construct and develop the informational accounting system. This system may be developed via the most advanced universal ways (merise). The research has concluded a number of results and recommendations, one of which is the need to complete the process of automatic processing in two steps: The first step: collecting and analyzing documents and their archives. The second step: using comprehensive automatic processing where the staffs are more receptive of the idea, so they contribute in offering advice and useful information to the analysis group.